Tailoring treatment: dog breed status influences pain assessment and treatment in emergency veterinary care - Caddiell, Rachel M. P.; White, Philip A.; McNamee, Eleanor H.; Lynch, Alex M.; Lascelles, B. Duncan X.; Gruen, Margaret E. (Frontiers in Pain Research, 2025)
BackgroundSeveral studies have demonstrated that veterinarians hold breed-specific beliefs about canine pain sensitivity. However, it remains unknown whether these beliefs impact how veterinarians recognize and treat pain in a clinical setting. Therefore, the objective of this study was to determine if there were differences in the assessment and treatment of pain across patients admitted to a veterinary emergency room (ER) from different breeds.MethodsVeterinary ER records were retrospectively analyzed to evaluate the effects of breed on the assessment and treatment of pain in canine patients admitted to a single academic ER over a two-year period. Extracted data included patient signalment and information documented in medical evaluations completed by ER clinicians.ResultsThe final sample included records from 3,744 patients across 69 breeds/breed types. Patient breed and the service the patient was transferred to from the ER were significantly explanatory for differences observed in pain scores and pain management plans assigned. The effect of breed and transfer service remained robust when accounting for covariates.Conclusions and clinical relevanceCertain breeds were assigned pain scores lower than average, while other breeds were assigned higher than average pain scores despite a lack of evidence that these breeds presented with less or more painful conditions. As breed-specific beliefs do not align with experimental measures of pain sensitivity, the present findings have implications to help refine pain education and medical decision-making and ultimately improve patient care.